(untitled) (Northern International Medical College Journal, 2020)
Background : In Bangladesh about 67% of under-five mortality is neonatal mortality. One of three major causes of neonatal morbidity and mortality is septicemia. Recently there is increasing incidence of multidrug resistant neonatal organisms which is alarming. Objective : The aim of this study was to see the bacteriological profile and drug sensitivity pattern of neonatal septicemia. Methods : This prospective observational study was done in Dhaka Shishu (children) Hospital over one-year period from June 2018 to May 2019. The admitted neonates were suspected as neonatal septicemia considering the risk factors, clinical profile and investigations (CBC, CRP etc.). Blood from all suspected neonatal septicemia cases were sent for culture and drugs sensitivity along with others necessary investigations. Then data was analyzed with SPSS version-20. Results : Among the suspected cases only 111(10%) patients were culture positive. Preterm were 77(69%) and term 34(31%). One hundred six cases (95%) had sepsis with gram negative organisms and 5(5%) had sepsis with gram positive organisms with more predominant of Klebsiella (76,68%) followed by Acinetobacter (16,14%), Pseudomonas (6,5%), Escherichia coli (3,3%). Majority 80 (72%) cases had Early onset neonatal sepsis (EONS). Klebsiella (57, 51%) was more common organism followed by Acinetobacter (11,10 %) causing EONS and in late onset neonatal sepsis (LONS), similar type of causative organism were found. Ampicillin, Gentamicin and Ceftazidime were mostly resistance to gram negative organisms - 104(94%), 99(89%) and 93(84%) respectively. Besides these, Amikacin (104,94%), Imipenem (85, 77%) and Ciprofloxacin (73, 66%) were more resistance. Klebsiella in 17 cases and Acinetobacter in 4 cases were resistant to all commonly used antibiotics. Conclusion : Klebsiella followed by Acinetobacter and Pseudomonas are now common pathogens of neonatal septicemia found in this study. Ampicillin, Gentamicin and Ceftazidime are more resistant to most of the organisms causing neonatal sepsis. Imipenem is alarmingly resistant. In 19% cases, the organisms are resistance to all commonly used antibiotics. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 427-431